Fundações de apoio - regime jurídico - autonomia universitária - Almeida, Thomas Augusto Ferreira de (2013)
This work intends to elaborate an analysis of the legal treatment about the support foundations of the Federal Institutions of Higher Education (IFES), highlighting its unique conformation among the entities of the Third Sector. It will be demonstrated his special approach to the legal public regime resulted from recent legislative changes introduced by Law No. 12,349, of 15/12/2010, which significantly changed the law of the support foundations, Law No. 8958 of 20/12/1994. The origin of the support foundations will be contextualized within the constant design of the government seeking in private entities the flexibility of administrative management for implementation of the tasks assigned to it. This runway to the private legal regime, sharply occurred after the 1990s by the introduction of management administration as government policy, will be addressed from the perspective of the federal public universities and university autonomy in administrative, financial and patrimonial aspects. The dependence between the support foundations and IFES supported and the usefulness of its partnerships especially in university extension activities will also be the subject of reflection in this work. We will develop our study from the history of public universities and the growth of the Third Sector after the 1990s, going to the evolution of the legislative associated with the precedents of the Court of Audit in Brazil (Tribunal de Contas da União). At the end, will be examined the vulnerabilities and strengths of the current legal arrangement provided by law for the relationship between support foundations and IFES supported